Post-pandemic pressures in UK higher education: a qualitative study of neoliberal impacts on academic staff and the unavoidable truths - Jones, Caroline Sarah; Bell, Huw (Frontiers in Education, 2025)
IntroductionConsiderable research has established that the COVID-19 pandemic resulted in increased mental health and wellbeing challenges amongst university students in the UK. This empirical research investigates frontline staff perspectives of the pandemic to establish the main pressures experienced post-pandemic.MethodsParticipants from central service teams and academic staff (n = 23) provided qualitative insights via interviews and focus groups.ResultsThe results were thematically analysed and suggest that marketisation and neoliberal practices are increasing pressure on academic staff, affecting their ability to implement relational pedagogical practices due to increasing duties and time pressures. Staff working frontline with students who are presenting with higher levels of mental health and wellbeing contribute to significant challenges post-pandemic.DiscussionRecommendations are that the role of frontline staff is reviewed/restructured to reduce pressure to mitigate staff burnout, and to reduce over reliance on staff emotional labour. Staff wellbeing and training post-pandemic needs to be reviewed by Higher Education Institutes (HEI). These original insights into the pressures experienced by staff in the post-pandemic context will be of interest to staff, management, human resources, and HEIs as they discuss candidly the unavoidable truths of the challenges faced post-pandemic.